Socio-technical imaginary of the fourth industrial revolution and its implications for vocational education and training: a literature review - Avis, James [Verfasser] (My University, 2018)
"This literature review engages with a diverse and sometimes contradictory body of work, employing an analytic stance rooted in policy scholarship. It discusses rhetorical constructions of the Fourth Industrial Revolution (4th IR), locating these in understandings of the economy rooted in a neo-liberalism which rests upon a capitalist terrain. The 4th IR is an ideological construct which reflects specific material interests and has particular implications for education and training. The 4th IR's association with digitalisation and artificial intelligence is ambivalent. For some writers, this leads to technological unemployment while for others, even though there is labour market disruption, there is no employment crisis that cannot be resolved. The strong connection between the 4th IR and labour market requirements is softened by those writers who adopt a qualitative analysis of advanced manufacturing work. These scholars suggest that the relationship between technology and skill is rather more complex than the protagonists of technological unemployment describe. Neo-Marxist writers develop a qualitatively different account of the current conjuncture to the imaginary of the 4th IR. In this instance, the analysis turns towards the elimination of labour from paid employment, together with the falling rate of profit and bypasses the former arguments. This review concludes by arguing that technology and artificial intelligence are entwined with social relations, being sites of class struggle. How this is played out is an outcome of the balance of power, not only within the social formation but also globally. How far the development of the forces of production is compatible with capitalist relations is a moot point, as this is also a site of struggle. The paper draws out the implications for VET and considers progressive educational responses. However, such a practice needs to be set within a broader politics that is committed to the development of a socially just society." (author's abstract; BIBB-Doku)
Keywords: G 2.2.1 Technologisierung; G 2.3 Wandel von Arbeit & Wirtschaft; Industrie 4.0; Arbeitsmarkt; Arbeitsmarktforschung; Berufsbildung; Neoliberalismus; Kapitalismus; Literaturanalyse